The Effect of Sports Performance Entrepreneurial Project by Entrepreneurial Spirit - Song, Shuxiong (Frontiers in Psychology, 2022)
This study aims to analyze the effect of entrepreneurship on the growth of entrepreneurial enterprise projects, so that entrepreneurial projects can improve entrepreneurial performance, promote social and economic development, and improve resource allocation. Firstly, entrepreneurship is explored to analyze the role in the growth of entrepreneurial enterprise projects. The entrepreneurial essence requirements based on entrepreneurship provide a theoretical basis for sports performance entrepreneurship. Secondly, the idea and process of sports performance entrepreneurship are described. A growth model of sports performance entrepreneurship based on entrepreneurship is established. Finally, the entrepreneurs who started sports performances are considered to investigate the enterprises participating in a sports competition performance. The influence of six elements of entrepreneurship on the progress and performance of sports performance entrepreneurial projects is analyzed. The results show that the spirit of risk-taking, need for achievement, and professionalism in entrepreneurship have the highest consistency, all above 0.90. It shows that entrepreneurship can promote the sports performance entrepreneurship project, and the subjects have a high entrepreneurial spirit. The adventurous spirit has more than half of the coverage of sports performance entrepreneurial projects. The coverage rate of knowledge literacy, innovative spirit, advanced action, achievement needs, and professionalism in sports performance entrepreneurial projects are all about 0.43. Innovation, risk-taking, and creativity can boost the performance of sports performance entrepreneurial projects. Enterprise size has little influence on sports performance. These conclusions have reference significance for the impact of sports entrepreneurial project performance.